2020
DOI: 10.1002/jmv.26210
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus envelope glycoprotein B, H, and N polymorphisms among infants of Shanghai area in China

Abstract: Human cytomegalovirus (HCMV) is the leading cause of congenital infection and an opportunistic pathogen capable of establishing lifelong latency. In the present study, we aimed to investigate the distribution of glycoprotein B, H, and N in infants of Shanghai and correlate the genotype with active and latent HCMV infection. A total of 129 urine samples were collected between August 2014 and December 2015 from infants under 3 years with HCMV infection. Nested PCR was used to amplify the regions of UL55 (gB), UL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
1
5
2
Order By: Relevance
“…The genotypes detected in this study are consistent with a previous study in Japanese infants [30], but different from studies in Indian [31], Polish [32] , and Italian [33] infants (17.64%, 15.40%, 32.50% for gB2, and 5.8, 28.8, 5.0% for gB4, respectively). Amazingly, Compared with reports from the different provinces in China, our results were similar to those of Shanghai [34], but different from those of Wuhan [35] and Zhejiang [36,37], which reported high frequencies of gB2 genotype (12.5%, 17.72% and 13.4%, respectively). These differences show that people in different regions have different susceptibilities to each type of HCMV, and the identification of the gB genotype helps understand the dominant epidemic strains.…”
Section: Discussioncontrasting
confidence: 61%
“…The genotypes detected in this study are consistent with a previous study in Japanese infants [30], but different from studies in Indian [31], Polish [32] , and Italian [33] infants (17.64%, 15.40%, 32.50% for gB2, and 5.8, 28.8, 5.0% for gB4, respectively). Amazingly, Compared with reports from the different provinces in China, our results were similar to those of Shanghai [34], but different from those of Wuhan [35] and Zhejiang [36,37], which reported high frequencies of gB2 genotype (12.5%, 17.72% and 13.4%, respectively). These differences show that people in different regions have different susceptibilities to each type of HCMV, and the identification of the gB genotype helps understand the dominant epidemic strains.…”
Section: Discussioncontrasting
confidence: 61%
“…A chinese study ( 65 ) also found a predominance of gH1 genotype in cCMV children suffering SNHL. We observed in a previous study that the gH1 genotype was predominant in infants with active CMV infection, while gH2 was more prevalent in children with latent infection ( 55 ). All these observations suggest that gH1 may be involved in early infancy hearing loss due to cCMV infection.…”
Section: Discussionmentioning
confidence: 71%
“…A nested PCR with two pairs of primers were used to amplify the UL55, UL75 and UL73 gene fragment as described previously ( 55 ). All the positive products of nested PCR were sent out for sequencing (Sangon or Tsingke Biotechnology Co., Ltd.).…”
Section: Methodsmentioning
confidence: 99%
“…The first five genotypes have been detected in Asia, Europe, and North America. However, their geographic distribution differs: gB1 is the most prevalent genotype in Asia and Egypt [ 6 , 14 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]; gB1 and gB2 are frequently detected in North America [ 39 , 40 , 41 , 42 , 43 , 44 , 45 ]; in South America, the most frequent genotypes were gB1 and gB2 [ 9 , 10 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ] whereas gB1, gB2, and gB3 are commonly observed across Europe (with the exception of Serbia where gB4 is the most prevalent genotype) [ 55 , 56 , 57 , 58 , 59 ...…”
Section: Discussionmentioning
confidence: 99%